IMPACT OF RECIPROCAL CROSS AND HETEROSIS PHENOMENON ON VARIOUS TOMATO TRAITS - Shilan A. H. Chawsh; H. A. Arkwazee (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This research aimed to study the impact of the reciprocal cross and heterosis phenomena on numerous tomato (Solanum lycopersicum L.) characteristics. Fifty-one different traits were measured, including leaf, shoot, root, flower, fruit, yield and yield components, and physiochemical characteristics. The results showed that reciprocal crosses, such as plant mass, petal length, cone length, pistil length, fruit width, fruit length, single fruit weight, fruit flesh weight, seed and placenta weight, number of fruits locules, fruit calyx weight, number of days to flower, total sugar, ascorbic acid, anthocyanin, and total phenolic concentration, significantly influenced various traits. In addition, the results showed that several traits showed positive high parent heterosis, which are the sepal length, pistil length, flower fresh weight, flower dry weight, flower moisture content, number of clusters per plant, number of flowers per plant, number of flowers per cluster, number of fruits per cluster, fruits number per plant, total fruits weight per plant, leaf length, leaf fresh weight, leaf dry weight, number of branches per plant, plant height, plant mass, ascorbic acid, total carotene, and anthocyanin. These results will be significantly helpful for the future breeding program, especially for developing F1 cultivars with significant quality and quantity.